1997
DOI: 10.1159/000227714
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Metallothionein Correlates with Chemoresistance to Cisplatin and Prognosis in Esophageal Cancer

Abstract: The aim of this study was to determine the correlation of metallothionein (MT) expression with resistance to cisplatin and to identify prognostic factors in esophageal cancer. Immunostaining for MT was performed on the specimens of squamous cell carcinoma of the esophagus resected from 68 patients with curative intent. The expression of MT was evaluated in terms of clinicopathologic variables, effect of cisplatin, and the patients’ survival. Overexpression of MT in the tumor was found in 70.6% of the patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 18 publications
0
40
1
1
Order By: Relevance
“…In stage IV melanoma patients, anticancer drugs, as well as irradiation therapy, are known to often show only a humbled rate of clinical responses. These therapeutic failures may partially be related to an enhanced MT overexpression in tumour cells, although the involvement of MT in conferring resistance to chemotherapeutics still remains under discussion (Chin et al, 1993;Hishikawa et al, 1997;Okazaki et al, 1998;Cherian et al, 2003). As a variety of endogenous factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In stage IV melanoma patients, anticancer drugs, as well as irradiation therapy, are known to often show only a humbled rate of clinical responses. These therapeutic failures may partially be related to an enhanced MT overexpression in tumour cells, although the involvement of MT in conferring resistance to chemotherapeutics still remains under discussion (Chin et al, 1993;Hishikawa et al, 1997;Okazaki et al, 1998;Cherian et al, 2003). As a variety of endogenous factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, MT are involved in many physiological and pathophysiological processes such as the intracellular storage, transport and metabolism of heavy metal ions; they regulate essential trace metal homeostasis and play a protective role in heavy metal detoxification reactions (Miles et al, 2000;Simpkins, 2000). They can protect cells against UV-/ionic radiation (Hansen et al, 1997;Hanada et al, 1998;Reeve et al, 2000) as well as cytotoxic alkylating agents including chemotherapeutics (Chin et al, 1993;Hishikawa et al, 1997;Okazaki et al, 1998;Sunada et al, 2005), modulate oxygen free radicals and nitric oxide and inhibit apoptosis (Tsangaris and Tzortzatou-Stathopoulou, 1998). The synthesis of MT is induced by group II heavy metal ions as well as by endogenous factors such as glucocorticoids, cytokines (interleukin (IL)-1 or IL-6, interferon g (IFNg), tumour necrosis factor a (TNF-a)) or vitamin D 3 (Karin et al, 1985;Karasawa et al, 1987;Schroeder and Cousins, 1990;Sato and Sasaki, 1992;Nishimura et al, 2000).…”
mentioning
confidence: 99%
“…The results of these clinical trials suggest that it might be necessary to select the most effective therapy for each case in order to improve survival of patients with OSCC, especially advanced OSCC. Recent studies have elucidated several molecules, such as p53, GST-π and metalothionein, responsible for sensitivity to cisplatin (Timmer-Bosscha et al, 1993;Rusch et al, 1995;Hishikawa et al, 1997). More recently, nm23-H1 has been reported to correlate directly with sensitivity to cisplatin as well as other alkylating agents by transfection assay (Ferguson et al, 1996) and the expression of nm23-H1 protein has been shown to correlate inversely with prognosis of patients with ovarian carcinoma after cisplatin-based chemotherapy (Scambia et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…To the contrary, Öfner et al (1994) reported that MT overexpression in colorectal carcinoma was associated with better clinical outcome and tumour stages. Therefore, MT overexpression may be paradoxically associated in some tumours with better clinical outcome.Tumour MT level also has been reported to correlate with resistance to anticancer reagents (Kelley et al, 1988;Kasahara et al, 1991;Chin et al, 1993;Kondo et al, 1995;Hishikawa et al, 1997). In oesophageal SCC, we already reported that MT protein expression might be a significant determinant of prognosis, in particular, associated with cisplatin resistance (Hishikawa et al, 1997).…”
mentioning
confidence: 81%